REVITALISASI SENI KRIYA INDONESIA Sumartono ABSTRACT - Mr. Sumartono (Ars: Jurnal Seni Rupa dan Desain, 2007)
"Craft" has a long history in Indonesia. The arrival o f religions (Hindu, Buddhism, and Islam) anddifferent groups (Chinese and westerners) to Indonesia influenced not only to the pattern but also lo theprocess o f creation o f this artwork. These influences provide a neio spirit/life to the Indonesian "craft".Hozoever, Indonesian artists still maintain the " traditional" forms and patterns. They only lake someaspects o f these other cultures and combine them with local culture. Because o f artists'creativity, Indonesian"craft" is able to exist fo r a longer time. Moreover, in order to maintain its existence, the Indonesian "craft~artists are expected to takepart in the discourse o f visual art in IndonesiaKeywords: craft (high art), revitalisation, theory o f change